PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS MODEL PEMBELAJARAN NOVICK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI FLUIDA STATIS DI KELAS XI SMA - Novriandami, Aldila; Yennita, Yennita; M. Syafi’i, M. Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning device developed is a physics learning tool based on the Novick model to improve students' conceptual understanding of class XI SMA on static fluid material, consisting of Learning Implementation Plans (RPP), Student Worksheets (LKPD), and concept understanding test instruments. The purpose of this research is to produce a valid Novick model-based physics learning device that is used to improve students' conceptual understanding of class XI SMA on static fluid material. This research is expected to be a reference for making innovative learning tools and can be used as a basis in the teaching and learning process so that learning objectives can be achieved. This type of research is Research and Development (R&D) using a 4D model. This research is only limited to the development stage. The research instrument used was the RPP validation assessment sheet, LKPD, and the concept understanding test instrument used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results showed that the Novick model-based physics learning device was declared valid with the overall score of the device being 3.37 with a high category, so it was declared feasible to be used for teaching in class XI SMA in an effort to improve students' understanding of students' concepts on static fluid material.Key Words: Physics Learning Tools, Novick Model, conceptual understanding, Static Fluid.